The synthesis of a hexameric expanded hemiporphyrazine - Briana R. Schrage (2019)
© 2019 World Scientific Publishing Company. Although the chemistry of expanded porphyrins is well developed, there has been significantly less work on expanded isoindoline based macrocycles such as hemiporphyrazines. In this report we present the synthesis and characterization of a new hexameric expanded hemiporphyrazine which we refer to as hexahemiporphyrazine. The synthesis incorporated bis(6-amino-2-pyridyl)amine as a starting material, which could be produced from 2,6-diaminopyridine using melt reaction conditions. Bis(6-amino-2-pyridyl)amine can adopt a three different conformations, two of which are observed in the free base and protonated form, and the third in the backbone of hexahemiporphyrazine. Reaction of bis(6-amino-2-pyridyl)amine and diiminoisoindoline in the presence of a catalytic amount of BF3 produces the hexihemiporphyrazine macrocycle, which was characterized spectroscopically and by X-ray crystallography. Structure elucidation reveals two inverted pyridine rings in a configuration reminiscent of that seen in hexaphyrin, however hexahemiporphyrazine lacks cross conjugation across the macrocycle.